PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SELARAS CIPTA BERSATU (SCB) TANGERANG - Lusi Yaniwati Zega; Pancagaluh Ratnasih (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of Motivation and Discipline on Employee Performance at PT. Aligned Cipta Bersatu either partially or simultaneously. The method used is a quantitative method with a comparative causal approach, namely identifying the influence of one variable on another variable. The sampling technique used was the census method or saturated sample method using a sample of 110 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The significance value of the influence of Motivation (X₁) on employee performance (Y) is 0.000 < 0.05 t value > t table or (7,663 > 1.993). Thus, H1 is accepted, meaning that there is a partially significant influence between the influence of motivation (X₁) on employee performance (Y) at PT. Selaras CiptaSatu. The significant value for the influence of discipline (X₂) on employee performance (Y) is 0.000 < 0.05 and the calculated t value > t table or (5.945 > 1.993). Thus, H2 is accepted, meaning that there is a partially significant influence between the work environment (X₂) on employee performance (Y) at PT. Selaras CiptaSatu. The significance value for the influence of Motivation (X1) and Work Discipline (X2) on employee employee performance (Y) is 0.000 < 0.05 and the value of Fcount > Ftable or (35.345 > 2.730). Thus and H3 is accepted. This means that there is a significant simultaneous influence between the influence of motivation (X₁) and discipline (X₂) on employee performance (Y) at PT. Aligned to United Creation.